Perfluorinated phosphine and hybrid P-O ligands for Pd catalysed C-C bond forming reactions in solution and on Teflon supports - Baker, Robert; Begum, Farzana; Ikram, Muhammad; Twamley, Brendan (My University, 2019)
The synthesis of two types of phosphine ligands that feature perfluorinated ponytails is reported. A bidentate (RfCH2CH2)2PCH2CH2P(CH2CH2Rf)2 (Rf = CF3(CF2)n; n = 5, 7) and an alkoxyphosphine made by ring opening a fluorous epoxide, RfCH2CH(OH)CH2PR2 (Rf = CF3(CF2)7), have been prepared and spectroscopically characterised. The electronic effects of the fluorous chains have been elucidated from either the 1JPt–P or 1JP–Se coupling constants in Pt(II) or phosphine selenide compounds. Whilst the bidentate phosphines do not give stable or active Pd catalysts, the hybrid ligand does allow Susuki, Heck and Sonogashira catalysis to be demonstrated with low catalyst loadings and good turnovers. Whilst a fluorous extraction methodology does not give good performance, the ligand can be adsorbed onto Teflon tape and for the Suzuki cross coupling reaction the catalytic system can be run 6 times before activity drops and this has been traced to oxidation of the ligand. Additionally the crystal structure of the hybrid phosphine oxide is reported and the non-covalent interactions discussed.
Keywords: Perfluorinated ponytails; Alkoxyphosphine made